Perception of graduates about the teaching-learning process in a Private University - Remuzgo Artezano, Anika (2018)
Introduction: The University has the responsibility to strengthen the social, economic and political development of the country, it forms students with a vision of leadership, in order to achieve success and guide their work environment. Objective: The objective of the study was to determine the perception of the graduates about the teaching-learning process according to dimensions: curricular plan, teaching-learning strategies, development of activities and evaluation in a Private University. Materials and methods: The research is of a descriptive, transversal and quantitative approach, seeks to answer problems related to the perception of the graduates about the teaching-learning process according to dimensions. Results: In the results, the structured dimensions in the Learning Teaching Factor are characterized, based on the Conceptual Framework of the SINEACE Model. Dimension: Curricular Plan, the perception that the graduates have in relation to the Curricular Plan dimension is good, representing 48.3% with an excellent tendency. In this regard, the graduates have manifested an intermediate position, due to the variations that the curricular Plan has presented, which they considered positive for their professional development. Conclusion: It was also possible to conclude regarding the teaching-learning process: disagreement with the curricular plan, expressing that there is an inadequate sequence of the courses and, regarding the teaching and learning strategies, they refer that the methodology of the sessions was traditionally predominant use only of multimedia.